Haemato-Biochemical Studies Before and After Ovario Hysterectomy in Bitches Affected with Pyometra - Hadiya; Patel, Dipak M.; Parikh, Pinesh V.; Rao, Neha (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This study was conducted on 18 bitches; 10 affected with pyometra and 8 normal healthy bitches to evaluate and compare the haemato biochemical profiles before and after surgical intervention. The blood samples were collected from confirmed cases of canine pyometra and healthy bitches just before and on day 8th and 15th after surgery. The mean values of haemoglobin, packed cell volume, total erythrocyte count, total platelet count were significantly (p <0.01) lower, and erythrocyte sedimentation rate and total leucocyte count were significantly (p <0.01) higher in bitches affected with pyometra as compared to healthy ones on day 0. These differences gradually narrowed down on day 8th and 15th post-operative with improvement in profile of operated pyometric bitches. The mean neutrophil count was significantly increased, whereas the values of lymphocytes, monocytes and eosinophils were decreased in bitches with pyometra than in healthy ones, which gradually normalized in post-operative period. Significantly (p <0.05) higher values of plasma urea nitrogen (46.13 ± 6.79 vs. 24.32 ± 5.16 mg/dl), creatinine (1.92 ± 0.42 vs 1.14 ± 011 mg/dl) plasma total protein and globulin (4.87 ± 0.27 vs 2.85 ± 0.19 g/dl) with lower A:G ratio (0.51 ± 0.03 vs 0.99 ± 0.10) were recorded in bitches with pyometra as compared to healthy ones, which declined non-significantly by 8th and 15th day post-operative in affected bitches. There was significant decline in the plasma levels of total cholesterol and enzymes aspartate amino transferase and alanine aminotransferase in bitches with pyometra at 8th and 15th day post-operative as compared to pre-operative values, however the differences between healthy and affected bitches were statistically non-significant, perhaps due to wide variation in the profiles of individual animals. It is concluded that haemato-biochemical profile in conjunction with clinical signs can be used to predict the severity of canine pyometra.